Andrographolide suppresses RANKL‐induced osteoclastogenesis in vitro and prevents inflammatory bone loss in vivo. (February 2014) - Zhai, Z J; Li, H W; Liu, G W; Qu, X H; Tian, B; Yan, W; Lin, Z; Tang, T T; Qin, A; Dai, K R
<x xml:space="preserve">Abstract</x> Background and Purpose Osteoclasts play a pivotal role in diseases such as osteoporosis, rheumatoid arthritis and tumour bone metastasis. Thus, searching for natural compounds that may suppress osteoclast formation and/or function is promising for the treatment of osteoclast‐related diseases. Here, we examined changes in osteoclastogenesis and LPS‐induced osteolysis in response to andrographolide (AP), a diterpenoid lactone isolated from the traditional Chinese and Indian medicinal plant Andrographis paniculata. Experimental Approach Effects of AP on osteoclast differentiation and bone resorption were measured in vitro. Western blots and RT‐PCR techniques were used to examine the underlying molecular mechanisms. The bone protective activity of AP in vivo was assessed in a mouse model of osteolysis. Key Results AP concentration‐dependently suppressed RANKL‐mediated osteoclast differentiation and bone resorption in vitro and reduced the expression of osteoclast‐specific markers, including tartrate‐resistant acid phosphatase, calcitonin receptors and cathepsin K. Further molecular analysis revealed that AP impaired RANKL‐induced NF‐κB signalling by inhibiting the phosphorylation of TGF‐β‐activated kinase 1, suppressing the phosphorylation and degradation of IκBα, and subsequently preventing the nuclear translocation of the NF‐κB p65 subunit. AP also inhibited the ERK/MAPK signalling pathway without affecting p38 or JNK signalling. Conclusions and Implications AP suppressed RANKL‐induced osteoclastogenesis through attenuating NF‐κB and ERK/MAPK signalling pathways in vitro, thus preventing bone loss in vivo. These data indicated that AP is a promising natural compound for the treatment of osteoclast‐related bone diseases.